PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN VIDEO TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATA PELAJARAN IPAS DI UPTD SD NEGERI 62 PAREPARE - Nur Diva Rahmadani; Muslimin; Nur Ilmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the extent to which the guided inquiry learning model assisted by instructional videos affects students’ critical thinking skills in the Integrated Natural and Social Sciences (IPAS) subject at UPTD SD Negeri 62 Parepare. The research employed a quantitative approach with a quasi-experimental design using a non-equivalent Pretest-Posttest control group design. The population consisted of all students at UPTD SD Negeri 62 Parepare, totaling 279 students. The sample comprised 50 students, with Class IV-A serving as the experimental group (26 students) and Class IV-B as the control group (24 students). Data were collected through a critical thinking skills test administered before (pre-test) and after (post-test) the treatment. The results of inferential statistical analysis using the Independent Sample T-Test showed a significance value (Sig. 2-tailed) = 0.000 < 0.05, indicating that H₀ was rejected and H₁ was accepted. This means there was a significant difference in critical thinking skills between students in the experimental and control classes. Therefore, it can be concluded that the guided inquiry learning model assisted by instructional videos has a significant effect on Students’ Critical Thinking Skills in the Subject of Science at UPTD SD Negeri 62 Parepare.